2016
DOI: 10.23986/afsci.51465
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in weather events critical for boreal agriculture: I Elevated temperatures

Abstract: Variation in temperature challenges crop production and animal farming. Elevated temperatures are often harmful, though may also open opportunities at high latitudes. Impacts depend on the vulnerability of the object, production system and their resilience to climatic variability. The station-wise temperature observations from the Finnish Meteorological Institute for a time period of 54 years (1961‒2014) were interpolated to a regular 10 km × 10 km grid covering the whole country. Several successive time slice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…As temperature along with sunlight strongly controls crop growth and development, the warmer GS may provide improved conditions for agriculture in high latitude regions where the GS is short (Linderholm ; Peltonen‐Sainio and Rajala ; Peltonen‐Sainio et al . , ). On the other hand, the wetter GS primarily alters crop growth, yield and quality, and also many agricultural activities like tillage, sowing, crop protection and harvesting (Peltonen‐Sainio et al .…”
Section: Resultsmentioning
confidence: 99%
“…As temperature along with sunlight strongly controls crop growth and development, the warmer GS may provide improved conditions for agriculture in high latitude regions where the GS is short (Linderholm ; Peltonen‐Sainio and Rajala ; Peltonen‐Sainio et al . , ). On the other hand, the wetter GS primarily alters crop growth, yield and quality, and also many agricultural activities like tillage, sowing, crop protection and harvesting (Peltonen‐Sainio et al .…”
Section: Resultsmentioning
confidence: 99%
“…This may facilitate complementarity between oat and pea as companions in intercrops. For example, risk of drought episodes -often with coinciding elevated temperatures -is particularly high in early summer, after which it diminishes (Peltonen-Sainio et al 2016a, Peltonen-Sainio et al 2016b, Peltonen-Sainio et al 2016c: in years when drought occurs, oat yields are at higher risk than for pea, as elevated temperatures interfere with yield formation of oat, but favors that in pea ). As we found substantial variation in accumulation of precipitation and temperature across years and locations, it is apparent that the recorded variation in onset and duration of critical phenophases exposed companion crops to harmful and/or advantageous weather events differently.…”
Section: Discussionmentioning
confidence: 99%
“…Autumn sown crops can escape from the stresses typical for spring sown crops, such as early summer drought and elevated temperatures (Peltonen-Sainio et al 2011a) by having their root system in deep soil layers and having their most heat-vulnerable phenophases when the risk of heat waves is negligible (Peltonen-Sainio et al 2016b). Some studies have shown that crop phenology has advanced faster than sowing times (Siebert and Ewert 2012), which may further increase the escape capacity of winter crops for elevated temperatures, but make them more prone to night frost.…”
Section: Discussionmentioning
confidence: 99%
“…Depth and longevity of the soil frost are critical factors determining the first potential time for sowing. Weather conditions such as temperature and precipitation (Peltonen-Sainio et al 2016b, 2016c) may again either enable or postpone sowings depending on how well they favour operations, but also depending on production system, especially tillage method (Känkänen et al 2011, Soane et al 2012. As night frosts are often experienced after sowings under high latitude conditions, consideration of the risk for night frost may also be critical for the timing of sowing depending on crop.…”
Section: Introductionmentioning
confidence: 99%